Diagnostic Medievalism: The Case of Leprosy's Stigma - Jessica Chace (Disability Studies Quarterly, 2019)
This essay considers the longstanding stigma of leprosy diagnoses by looking at two case studies of leprosy in the modern era: a twentieth-century hagiography of Father Damien, a priest who contracted leprosy while caring for lepers on the Hawaiian island of Molokai, and a historical study of Carville, Louisiana, the site of the continental United States' only leper hospital for many decades. The analytical approach looks carefully at forms of description that are especially "medievalist" in nature—for example, the label of "martyr" that the author places on Father Damien or the carnivalesque description of the Mardi Gras Masque held annually for Carville patients. In so doing, the essay argues that certain diseases and disabilities are prone to a kind of "diagnostic medievalism," or tendency to focus on the moralistic connotations rather than the medical causes of a disease, based on historical misconceptions and stereotypes.
Keywords: leprosy; Hansen& #x27; s disease; stigma; institutionalization; medievalism; Molokai; HI; Carville; LA